Concurrent classical and hypervirulent Klebsiella pneumoniae infection in distinct host niches revealed by a rapid nanopore whole-genome and plasmid sequencing method - Wang, Lu; Wang, Qiqi; Tang, Zizhen; Wang, Yuyun; Qu, Yuanqing; Wen, Danli; Zhong, Qiulei; Hu, Huan; Liu, Yuan; He, Miao (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThis study reports a rare case of dual-strain Klebsiella pneumoniae infection involving genetically distinct isolates from the lung and eye of a previously immunocompetent patient.MethodsA rapid nanopore sequencing workflow on the Gseq-500 platform was used for whole-genome and plasmid sequencing. Comparative genomic and phylogenetic analyses assessed isolate relatedness and identified virulence and resistance determinants.ResultsThe lung isolate (KP-L) belonged to the hypervirulent ST23/KL1 lineage and carried a large non-conjugative plasmid encoding rmpA, rmpA2, iuc, iro, and peg-344, together with chromosomal yersiniabactin. In contrast, the eye isolate (KP-E) was a classical ST133/KL116 strain lacking known hypervirulence markers but harboring plasmids encoding heavy-metal resistance genes. Despite the absence of hypervirulence factors, KP-E caused severe endophthalmitis requiring enucleation, underscoring the pathogenic potential of classical strains in immune-privileged sites. Comparative genomic and phylogenetic analyses confirmed that the two isolates were not clonally related.DiscussionWe propose a plausible infection trajectory involving initial hypervirulent K. pneumoniae (hvKp) dissemination followed by niche-specific replacement by Classical K. pneumoniae (cKp) under antibiotic pressure. This case underscores that severe infections can arise from genetically “low-virulence” strains in certain host environments. Comprehensive genomic surveillance and aggressive clinical management strategies remain crucial for improving patient prognosis and understanding pathogen adaptation mechanisms within host niches.